2006
DOI: 10.1149/1.2216455
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitridation on Low-Frequency (1/f) Noise in n- and p-MOSFETS with HFO[sub 2] Gate Dielectrics

Abstract: The nitridation effects on low-frequency ͑1/f͒ noise in metallorganic chemical vapor deposited HfO 2 n-and p-metal oxide semiconductor field effect transistors ͑MOSFETs͒ are reported. Devices with a postdeposition anneal ͑PDA͒, performed after HfO 2 deposition, in a N 2 or NH 3 ambient were investigated. A significant variation in noise was observed when different PDAs were employed. Devices annealed with N 2 showed lower input referred noise S VG ͑ϳ125 V 2 /Hz͒ for ͉V G -V T ͉ ϳ 0.1 V, close to the ITRS speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 33 publications
3
8
0
Order By: Relevance
“…Using the conductance method, as before, the value of D it was calculated for the two forming gas annealed samples and the results are presented in table II. The obtained values (in the range of few 10 11 cm -2 ) are consistent with the values previously reported on similar samples that have undergone both DPN and FGA (10). The presence of nitrogen reduces the effectiveness of Si/SiO 2 interface passivation, so as the values of D it for these samples are higher than the ones expected for a Si/SiO 2 interface after FGA (~10 10 cm -2 ).…”
Section: Electrical Characterizationsupporting
confidence: 90%
See 1 more Smart Citation
“…Using the conductance method, as before, the value of D it was calculated for the two forming gas annealed samples and the results are presented in table II. The obtained values (in the range of few 10 11 cm -2 ) are consistent with the values previously reported on similar samples that have undergone both DPN and FGA (10). The presence of nitrogen reduces the effectiveness of Si/SiO 2 interface passivation, so as the values of D it for these samples are higher than the ones expected for a Si/SiO 2 interface after FGA (~10 10 cm -2 ).…”
Section: Electrical Characterizationsupporting
confidence: 90%
“…Although this value is quite high, it is consistent with the values reported in the literature from other groups on as-grown high-k dielectric films (7,8). However, it has been found that using a forming gas anneal at the end of the fabrication process, the value of D it can be reduced to as low as ~10 10 cm -2 (2,5,6,(9)(10)(11). This is due to the fact that hydrogen passivates effectively the interface between the Si substrate and the thin SiO 2 film underneath the Hf-based film, thus reducing the number of interface states.…”
Section: Introductionmentioning
confidence: 99%
“…One can note that the nitridation of the hafnium oxide prevents the penetration of dopants in the oxide. This has been proven in previous observations in planar transistors [7]. examples of the frequency normalized noise spectral density versus temperature behavior for a p and n-channel device.…”
Section: Resultssupporting
confidence: 68%
“…Some of the reasons for these discrepancies are higher trap density (6), interfaces between multilayer gate stacks (7) and nonuniform spatial (8) and energy (9) distribution of the high-k gate oxide traps compared to the conventional, native gate oxide.…”
Section: Low Frequency Noise Model For Mosfetsmentioning
confidence: 99%